2016
DOI: 10.1039/c6em00072j
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure to arsenic in UK private water supplies: toenail, hair and drinking water concentrations

Abstract: Chronic exposure to arsenic (As) in drinking water is an established cause of cancer and other adverse health effects. Arsenic concentrations >10 μg L(-1) were previously measured in 5% of private water supplies (PWS) in Cornwall, UK. The present study investigated prolongued exposure to As by measuring biomarkers in hair and toenail samples from 212 volunteers and repeated measurements of As in drinking water from 127 households served by PWS. Strong positive Pearson correlations (rp = 0.95) indicated stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 48 publications
(74 reference statements)
0
19
0
Order By: Relevance
“…Lastly, an independent external measure of exposure, e.g. drinking water analyte concentrations [ 28 ] could be used as an assessment criterion, but was not used in this study because of a lack of appropriate environmental data in NHANES.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, an independent external measure of exposure, e.g. drinking water analyte concentrations [ 28 ] could be used as an assessment criterion, but was not used in this study because of a lack of appropriate environmental data in NHANES.…”
Section: Introductionmentioning
confidence: 99%
“…7. Exposure to As in householders with PWS also depends upon the amount of water consumed, length of residency, seasonality of residency (e.g., permanent versus summer residents) as well as exposures through other routes (food, soil, air, dust) as explored in Cornwall and elsewhere in south west England [ 34 , 35 , 62 , 76 , 77 ]. Urine, hair and toenail samples taken from 127 households of the same cohort of PWS users indicated that As exposure via DW is likely a dominant source [ 34 , 35 ] as found by others [ 6 , 36 , 59 , 68 , 73 , 78 , 80 , 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Six percent of households failed the As PCV: the PCV and WHO guideline value [ 32 ] for As in PWS is 10 μg/L [ 32 , 33 ]. Biomonitoring of residents with PWS confirmed exposure to As through this exposure route, with high concentrations of As found in the urine, hair and toenails of some residents [ 34 , 35 ]. For PWS where DW was greater than 10 μg/L As, a strong correlation between DW As and urinary inorganic As was reported [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…1-hydroxypyrene glucuronide (1-OHPG), a polycyclic-aromatic hydrocarbon metabolite associated with ESCC in some studies 8 . Toenail clippings – useful longer-term biomonitoring matrices 9 - were taken from both large toes by research assistants and stored at room temperature. Biospecimen processing and storage took place at the Academic Model Providing Access to Healthcare (AMPATH) research laboratories.…”
Section: Methodsmentioning
confidence: 99%